Unlocking The Potential: Transforming Defense Through Human Capital Management - Aris Sarjito (Westscience Press, 2023)
This qualitative research study explores the adaptation of Human Capital Management (HCM) principles to meet the unique needs and challenges of defense organizations. The background highlights the increasing importance of optimizing HCM in defense to ensure operational readiness and adaptability in a dynamic security environment. The aim of this research is to provide insights into customizing HCM strategies for defense settings, including hierarchical structures, specialized skill requirements, and the imperative of operational readiness. Qualitative research methods using secondary data analysis were employed to examine existing literature, reports, and case studies related to HCM in defense. Findings reveal that customization of HCM in defense involves aligning leadership styles with HCM principles, overcoming cultural resistance, addressing bureaucratic constraints, and leveraging technological innovations for recruitment, training, and performance evaluation. Transformational and servant leadership styles emerged as conducive to HCM success in defense. Additionally, the study identifies relevant metrics such as retention rates, training effectiveness, promotion from within, employee engagement, and performance metrics, along with evaluation methods like benchmarking and cost-benefit analysis, as suitable for measuring HCM impact. These metrics can inform ongoing improvements, ensuring that defense organizations continuously adapt to meet evolving security challenges. In conclusion, this research sheds light on the potential of HCM to transform defense organizations, offering a roadmap for customizing strategies and leveraging leadership, technology, and evaluation methods to enhance human capital and national security.